Emulsion Designer Using Microfluidic Three‐Dimensional Droplet Printing in Droplet - Chen, Li; Xiao, Yao; Wu, Qinglin; Yan, Xiaoxiao; Zhao, Peng; Ruan, Jian; Shan, Jianzhen; Chen, Dong; Weitz, David A.; Ye, Fangfu (Small (Weinheim an der Bergstrasse, Germany), 2021)
Hierarchical emulsions are interesting for both scientific researches and practical applications. Hierarchical emulsions prepared by microfluidics require complicated device geometry and delicate control of flow rates. Here, a versatile method is developed to design hierarchical emulsions using microfluidic 3D droplet printing in droplet. The process of droplet printing in droplet mimics the dragonfly laying eggs and has advantages of easy processing and flexible design. To demonstrate the capability of the method, double emulsions and triple emulsions with tunable core number, core size, and core composition are prepared. The hierarchical emulsions are excellent templates for the developments of functional materials. Flattened crescent‐moon‐shaped particles are then fabricated using double emulsions printed in confined 2D space as templates. The particles are excellent delivery vehicles for 2D interfaces, which can load and transport cargos through a well‐defined trajectory under external magnetic steering. Microfluidic 3D droplet printing in droplet provides a powerful platform with improved simplicity and flexibility for the design of hierarchical emulsions and functional materials. Hierarchical emulsions are generated by microfluidic 3D droplet printing, the combination of microfluidics and 3D printing. Microfluidic 3D droplet printing in droplet has advantages of easy processing and flexible design in constructing hierarchical emulsions with tunable core number, size, and composition, and developing excellent‐performance delivery vehicles, which presents a powerful tool for both scientific researches and practical applications.